Fatwa MUI Nomor 4 Tahun 2003 Tentang Penggunaan Nama Kuliner Unik Perspektif Fikih - Muhammad Arfan Ahwadzy (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2024)
The uniqueness of culinary names in restaurants or eateries has led some of these names to carry negative connotations in the eyes of certain segments of society. Many culinary names, such as "Mie Gacoan," "Mie Setan," "Ceker Dajal," and others, can seem inappropriate or excessive. In light of this, the aim of this study focuses on MUI Fatwa Number 4 of 2003, which discusses the use of unique culinary names from an Islamic legal perspective. This research seeks to explore how the legality of a name is evaluated within Islamic law using the tools of Fiqh. It also examines the underlying values that govern the use of names in Islam. The research employs a library research method, drawing upon primary sources to formulate Islamic viewpoints based on the Qur'an, Hadith, Fiqh principles, and classical Islamic texts (Kitab Kuning). The findings conclude that, from a Fiqh perspective, MUI Fatwa Number 4 of 2003 prohibiting names in culinary contexts that suggest disbelief, falsehood, or refer to prohibited objects or animals is justified. This is because the meanings of such names are deemed inappropriate for food products. Furthermore, the Fiqh perspective on the values underlying food naming encompasses three important aspects: first, serving as an identity for the named item; second, acting as a distinguishing factor between different entities; and third, functioning as a form of prayer for the named item. Therefore, the Fiqh perspective assesses MUI Fatwa Number 4 of 2003 as aligned with the principles of Islam.